Scenario of General Anesthesia for Cesarean Section in Rural Tertiary Care Center in High Altitude Karnali Academy of Health Sciences - Bhattarai, Ramesh; Shah, Rajiv; Dhakal, Sita; Malla, Pragya; Sapkota, Srijana (Journal of College of Medical Sciences-Nepal, 2020)
Background: General anesthesia for cesarean section is being less popular for cesarean section in present days but sometime general anesthesia is inevitable. The aim of the study is to assess the trends of general anesthesia, indications, clinical outcome in mother and fetus in high altitude setting of tertiary care center of Nepal. Methods: We conducted descriptive cross-sectional study all cases of cesarean section in Karnali Academy of health Sciences (KAHS) located at high altitude over three years period in our institute. Data were retrieved from the hospital records during three fiscal year (Jan 1st 2017 to Jan Dec 31st 2019). The record of all the patients who underwent cesarean section under general anesthesia was reviewed for demographic details, indication of general anesthesia, trends for general and spinal anesthesia and maternal and neonatal outcome. Results: Out of total deliveries 2175, 309 (14.2%) cases account for cesarean section. Among them, 52 (17%) required general anesthesia . Eclampsia 19(36%) remain the major indication for General Anesthesia in cesarean section followed by failure of spinal anesthesia number 14 (26%) , cord prolapse six (12%), antepartam haemorrhage five (10%), spinal site infection four (8%), Khiphoscoliosis two(4%), Patients request two (4%). Use for general anesthesia technique was consistent for three years with slow rise in use of spinal anesthesia . There was no any anesthesia related maternal mortality and nine intraoperative neonatal Conclusions: General anesthesia practices are consistently required in rural high-altitude setup. Eclampsia is the commonest indication followed by failure of spinal anesthesia and cord prolapse. Neonatal outcome is still not good.